Unfeasible body mass index and its association with low haemoglobin concentration: a correlation study among undergraduate medical students - Khan, Tazeen; Khan, Zahid A.; Kochhar, Sonia; Singh, Baljinder; Goyal, Gurdev L.; Sharma, Ruby (International Journal of Research in Medical Sciences, 2018)
Background: Low hemoglobin concentration and unfeasible body mass index adversely affect the health of people, consequently increasing morbidity and mortality among them. Hemoglobin concentration among individuals is associated with their body mass index. The prevalence of iron deficiency anemia is higher among underweight and overweight/obese people compared to those with normal BMI. Thus, the present study aimed to determine the correlation between hemoglobin concentration and BMI of undergraduate medical students. Methods: A cross-sectional study was carried out among 210 undergraduate medical students. Body mass index was calculated and hemoglobin estimation was done by Sahli's hemoglobinometer. Correlation between hemoglobin concentration and body mass index of subjects was assessed by Pearson’s correlation coefficient. Results: Underweight students had lowest mean hemoglobin concentration and the mean hemoglobin concentrations increased significantly (p<0.001) with increase in the BMI of subjects. A highly significant positive correlation (r=0.307, p<0.001) between BMI and hemoglobin concentration was observed. Further, significant positive correlation was observed among males (r=0.268, p=0.013), students with normal BMI (r=0.283, p=0.003) and overweight students (r=0.415, p=0.035) only. Conclusions: Hemoglobin concentration and BMI show a positive correlation, however this correlation tends to become negative in obese individuals. As both low hemoglobin concentration and unfeasible body mass index have detrimental effects on the health, diligent screening and management of both is essential for better outcome.